Heuristic approaches for the flow-based set covering problem with deviation paths - Li, Shengyin; Huang, Yongxi (Transportation research. Part E, Logistics and transportation review, 2014)
•We develop heuristics for the multipath refueling location model.•We consider the impact of deviation paths, vehicle range on networks.•Numerical experiments show heuristic solution efficiency and effectiveness.•Heuristics are also applicable for other existing flow-based set-covering problem. A multipath refueling location model is developed to take into account the effects of vehicle range and multiple deviation paths. It is formulated as a mixed integer linear program, which is intrinsically difficult to solve with increase in the number of deviation paths and network size. This study is focused on developing heuristic approximation solutions, specifically the greedy-adding and greedy-adding with extension algorithms. These algorithms are shown to be efficient and effective to solve the model for the Sioux Falls network. The heuristics are also applied to locate electric vehicle charging stations in the state of South Carolina.